Studying thermodynamic properties of linear acenes molecules (C4n+2H2n+4) using hyper-Zagreb index. (3rd October 2019) - Alamoti, Somayeh Shafiee; Alaeiyan, Mehdi; Gilani, Alireza
Abstract: Let G = ( V, E ) be a simple connected graph with the vertex and edge sets respectively, V ( G ) and E ( G ). The hyper-Zagreb index of G is defined as HM ( G )= ∑ uv ∈ E ( G ) ( du + dv ) 2 over all edges uv of G, where du denotes the degree of the vertex u of G . In this paper, we calculate hyper-Zagreb index, for organic linear Acenes molecules ( C 4 n +2 H 2 n +4 ). Furthermore, we find a relationship between topological indices based on the number of rings and prediction the thermodynamic properties of Acenes family such as electron affinity, bond and gap energy by using Topological Indices Method(TIM).